Design and Analysis of a Permutation Strategy using 3D Chaotic Map - Panwar, K; Purwar, RK (International Journal of Computer Sciences and Engineering, 2019)
In Image encryption scheme, the permutation operation plays an important role in confusing the pixels of image and is used in combination with diffusion operation. This paper proposes an efficient 3D permutation strategy for color image that is free from sorting operation and is based on Lorenz map. It has good confusion properties than permutation algorithms that do not involve sorting operation and in comparison to permutation algorithms with similar security that involves use of sorting operation, the proposed method has lower complexity. Performance and Security of proposed permutation algorithm are analysed and results further justify that the permutation scheme is secure is computationally efficient for application in image encryption scheme.